Effect of Tiliacora triandra leaf extract on glycemic control in mice with high sugar intake - Wachiryah Thong-asa,; Prachayaporn Prasertsuksri,; Romgase Sakamula,; Theerayut Nimnuan, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Prediabetes is associated with sugar-sweetened beverages and sugar-rich processed foods. High sugar intake (HSI), which is represented as save dose, may silently alter the glycemic control. The present study investigated the effect of HSI and Tiliacora triandra (TT21) leaf extract on the glycemic control in mice. Eighteen male ICR mice were divided into three groups of Control-HSI, HSI-TT300 and HSI-TT600 that received 4 weeks of 30% glucose with a vehicle of T. triandra leaf extract 300 and 600 mg/kg, respectively. The blood glucose, serum insulin, glucose clearance, liver and muscle glycogen contents and tissue oxidative status were evaluated. The results showed that HSI increased the blood glucose (w2 and w3: p<0.05) and serum insulin levels (w3 and w4: p<0.05) with glucose intolerance (w4: 30, 60 and 90 min, p<0.05). T. triandra leaf extract reduced the blood glucose and serum insulin and increased the glycogen content in the liver and muscle tissues (p<0.05). We concluded that HSI silently induced an alteration of the glycemic control in the normal mice, and the T. triandra leaf extract nurtured the glycemic control in the HSI mice by lowering the blood glucose and serum insulin and increasing the liver and muscle glycogen contents, which indicated an involvement of peripheral insulin sensitivity.